Особливості структурного підходу при формуванні управлінського ефективного лідерства - Гура, Тетяна Віталіївна; Ігнатюк, Ольга Анатоліївна; Резнік, Світлана Миколаївна (Національний технічний університет "Харківський політехнічний інститут", 2024)
В публікації висвітлено результати дослідження лідерських якостей в процесі професійної підготовки студентів-іноземців технічного закладу вищої освіти. Особлива увага приділена якостям сучасного ефективного управлінця-лідера. Визначені шість ознак ефективних здібностей лідерів. В статті охарактеризовано особливості ефективного лідерства в бізнес-управлінні, військовій сфері тощо. В статті висвітлені пріоритетні напрямки розвитку ефективного лідерства. Представлені особливості структурного підходу при формуванні управлінського ефективного лідерства в закладі вищої освіти.

The results of a study of leadership qualities in the process of professional training of foreign students of a technical institution of higher education are highlighted in the publication. Special attention is paid to the qualities of a modern effective manager-leader. Six signs of effective leadership abilities have been identified. The features of effective leadership in business management, military sphere, etc. are described in the article. The priority directions for the development of effective leadership are highlighted in the article. The features of the structural approach in the formation of effective managerial leadership in a higher education institution are presented in the article.
Features of the structural approach to the formation of effective managerial leadership
Keywords: управління; управлінська компетентність; майбутні офіцери; технічний університет; ефективне лідерство; військове лідерство; заклад вищої освіти; management; managerial competence; future officers; technical university; effective leadership; military leadership; institution of higher education